PENGARUH PENDIDIKAN KESEHATAN MASALAH KESEHATAN REPRODUKSI TERHADAP SIKAP MENJAGA KESEHATAN REPRODUKSI PADA SISWI KELAS II MULTIMEDIA DI SMK KRIYA SAHID SUKOHARJO - -, Endang Dwi Ningsih; -, Ratna Indriati (Intan Husada : Jurnal Ilmiah Keperawatan, 2015)
Background: One of the factors that influence the of reproduction health issues is the  lack of  knowledge about reproductive  health knowledge. Related  to this the  researchers  interested  in  studying  about  the  influence  of    educating  reproduction health to the the reproductive  health maintain attitude toward the female students in class II Multimedia of SMK Kriya Sahid Sukoharjo.Objective: This  study  was  to  determine  the  influence  of  educating  reproduction  health  to  the reproductive  health  maintain  attitude  toward  the female  students  in  class  II  Multimedia  of  SMK  Kriya  Sahid  Sukoharjo.Method: Used  the  study  design  with  pre  experimental  design  with  the approaching method is one  group pretest postest design. The subjects were 30  class  II  Multimedia  students  of  SMK  Kriya  Sahid  Sukoharjo.  The  datas collected and analyzed by Paired t test with α 0,05.Results: The datas analyzed by Paired t test, SPSS version 18 with α = 5%         ( 0,05). The cunted t = - 9,560, p value is 0,000< 0,05. It mean Ha accepted and Ho rejected. Conclusion is the educating reproduction health has significant influence to the reproduction health maintain attitude of the female students class II Multimedia of SMK Kriya Sahid SukoharjoKeywords: Health Educating, Reproduction Health, Attitude in keeping Reproduction Health.